Quantification of phosphorus diffusion and incorporation in silicon nanocrystals embedded in silicon oxide. (12th June 2014) - Mastromatteo, M.; Arduca, E.; Napolitani, E.; Nicotra, G.; De Salvador, D.; Bacci, L.; Frascaroli, J.; Seguini, G.; Scuderi, M.; Impellizzeri, G.; Spinella, C.; Perego, M.; et al.
<x xml:space="preserve">Abstract</x> The interest toward the doping of semiconductor nanostructures has been increasing steadily, but a clear understanding must still be reached, due to challenging characterization issues. In this work, we focused on Si nanocrystals (NCs) embedded in SiO2, which represent the most scalable and one of the most interesting and studied systems, but where an accurate quantification of the evolution of dopant profiles is still lacking. High depth resolution time‐of‐flight SIMS with charge compensation has been used to extract secondary ion depth profiles relative to P and Si elements. The relative sensitivity factors of P in SiO2 and of P in a layer containing Si NCs approximately 4.2 nm in diameter, as well as non‐linearity of P intensity at high P concentrations, were determined by comparison with P dose data extracted by Rutherford backscattering spectrometry analysis. Transmission electron microscopy analyses were performed to characterize the NC size distribution and stability upon thermal annealing. As a final result, we obtained a measurement protocol able to extract with high accuracy fully calibrated P concentration profiles in the SiO2 matrix with embedded Si NCs. Copyright © 2014 John Wiley & Sons, Ltd.